Short-term outcomes of da Vinci Xi versus Si robotic systems for minor hepatectomies - Bianchi, Giorgio; de'Angelis, Nicola; Musa, Nicola; Beghdadi, Nassiba; Hentati, Hassen; Ammendola, Michele; Inchingolo, Riccardo; Laurent, Alexis; Sommacale, Daniele; Memeo, Riccardo (Acta Biomedica Atenei Parmensis, 2022)
Background: In the recent years, robotic technology has been drastically improved and the last generation of robotic platforms is hardly comparable with the earlier ones. The present study aims to investigate the short-term outcomes of minor hepatectomies performed with da Vinci Xi surgical system vs. Si surgical systems. Methods: Consecutive patients operated on between 2013 and 2020 in two referral centers were selected if underwent elective robotic minor hepatectomy (<3 consecutive segments) for primarily resectable benign or malignant lesions. Operative, postoperative, and cost outcomes were compared between the two groups by univariate and multivariate analyses. Results: Eighty-nine patients were selected (64 in the Si system vs. 25 in the Xi system group). Wedge resection was the most commonly performed procedure (49.4%). The Si system group showed a significantly greater total incisional length (+8.99 mm; p<0.0001) related to the use of a higher number of robotic/laparoscopic ports. Pedicle clamping was more frequent in patients operated on by the Xi system (80% vs. 21.9%; p<0.0001) but without group differences in ischemia duration when clamping. A significantly shorter time to flatus (-0.75 days; p=0.015) was observed for patients operated on by the Xi system, whereas no group differences were found for operative time, conversion rate, estimated blood loss, postoperative complications, mortality, use of analgesics, and costs. Conclusion: The da Vinci Xi system represents a technological advancement with a potential clinical relevance, although further studies are needed to clearly detect the clinical impact of the use of this robotic platform in liver surgery.